2014
DOI: 10.1016/j.biomaterials.2014.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Molecular factors in dendritic cell responses to adsorbed glycoconjugates

Abstract: Carbohydrates and glycoconjugates have been shown to exert pro-inflammatory effects on the dendritic cell (DC), supporting pathogen-induced innate immunity and antigen processing, as well as immunosuppressive effects in the tolerance to self-proteins. Additionally, the innate inflammatory response to implanted biomaterials has been hypothesized to be mediated by inflammatory cells interacting with adsorbed proteins, many of which are glycosylated. However, the molecular factors relevant for surface displayed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…al. 10 . Briefly, mass spectra of the glycoconjugates were determined using Matrix Assisted Laser Desorption Ionization (MALDI) Mass Spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…al. 10 . Briefly, mass spectra of the glycoconjugates were determined using Matrix Assisted Laser Desorption Ionization (MALDI) Mass Spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Babensee and coworkers (52) showed that the charge of a carrier can enhance DC maturation in response to glycoconjugates (Figure 2 e ). In this study, it was shown that the conjugate charge induced the second largest increase in proinflammatory DC maturation, falling behind only ligand density in potency (52).…”
Section: Effects Of Biomaterials On Immune Cells and Immunomodulamentioning
confidence: 96%
“…Recently, Babensee and coworkers (52) showed that the charge of a carrier can enhance DC maturation in response to glycoconjugates (Figure 2 e ). In this study, it was shown that the conjugate charge induced the second largest increase in proinflammatory DC maturation, falling behind only ligand density in potency (52). It has also been shown that the surface charge of NPs influences the adsorption of opsonins (and other plasma proteins), leading to macrophage recognition, which is followed by phagocytosis and elimination (53).…”
Section: Effects Of Biomaterials On Immune Cells and Immunomodulamentioning
confidence: 96%
See 1 more Smart Citation
“…Hotaling et al recently conducted a study on BSA conjugates of various glycans to clarify the molecular determinants (glycan composition, density, carrier cationicity) that influence DC responses. 103 …”
Section: Probing Glycan Functions In Innate Immunity With Glycomaterialsmentioning
confidence: 99%